FRI0108 Correlation between Cervical and Lumbar Spinal Instability in Patients with Rheumatoid Arthritis. (10th June 2014) - Sugimura, Y.; Miyakoshi, N.; Miyamoto, S.; Hongo, M.; Kasukawa, Y.; Shimada, Y.
Abstract : Background: Few studies have compared rheumatoid arthritis (RA)-related disorders of the cervical and lumbar spine. Objectives: The objectives of this study were to examine the correlation between cervical and lumbar spinal instability in RA patients and to evaluate the associated risk factors. Methods: From a total of 1, 663 patients registered in the Akita Orthopedic Group on Rheumatoid Arthritis (AORA), 128 patients [111 women, 17 men; mean age, 66 (41–84) years; mean disease duration, 14 (1–63) years] who underwent a radiographic examination were enrolled in this study. In the cervical spine, we defined instability as one of the following characteristics: (1) atlantodental interval (ADI) >3 mm, (2) Ranawat value <13 mm on a neutral plain radiograph, or (3) anteroposterior translation >3 mm at the subaxial cervical spine on an anteroposterior bending plain radiograph. In the lumbar spine, instability was defined as anteroposterior translation >3 mm on a neutral plain radiograph. The association between cervical and lumbar spinal instability was examined using Mantel-Haenszel statistics. The patients were classified into two groups: with cervical and/or lumbar spinal instability and without. The independent risk factors for cervical and/or lumbar spinal instability were then determined using multivariate logistic regression analysis. Results: Forty-three (33.6%) patients exhibited cervical spinal instability, and 47 (36.7%) patients exhibited lumbar spinal instability. Twenty-two patients (17.2%) exhibited both cervical and lumbar spinal instability. Instability of the lumbar spine was significantly greater in the group with cervical spinal instability than in the group without (OR: 2.46; 95% CI: 1.13–5.35). Cervical and/or lumbar spinal instability were significantly and independently associated with Steinbrocker's classification stage (OR: 1.62; 95% CI: 1.07–2.47) and disease duration (OR: 1.01; 95% CI: 1.00–1.01). Conclusions: Cervical and lumbar spinal instabilities in RA patients are correlated. Steinbrocker's classification stage and disease duration were independent risk factors for cervical and/or lumbar spinal instability in this study. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3989